Pengaruh ASI Eksklusif dan Susu Formula terhadap Berat Badan Bayi - Husnul Muthoharoh (Politeknik Kesehatan Kemenkes Mamuju, 2021)
The first and main nutrient intake of breastfed infants is urgently needed for the process of growth and development. The purpose of this is to find out the influence of exclusive breast milk and formula on the baby's weight in Posyandu Jatipayak Village Modo-Lamongan. This study uses an observational design of case-control analytic approach that aims to distinguish weight infants at age 1-6 months of exclusive breastfeeding and infant formula. The research instrument was used in the form of interviews and observations with a population of all infants aged 1 – 6 months who qualify for inclusion criteria who were 30 toddlers and using a simple random sampling technique. Results of research that babies who are breastfed exclusively have the majority of normal weight increase of 60%, whereas infants who received formula milk most have an abnormal weight gain of 86.67%. Based on the results of Chi-Square X² = 5.167> 3.841. This study rejects the Ho that proves that there are differences in body weight in infants aged 1-6 months of exclusive breastfeeding and infant formula. The result of this research is expected mothers to provide breast milk as the best food for babies up to age 6 months.